Photoluminescence of core-shell nanoparticles made from yttrium stabilized zirconia powder grain coated with alumina - Gonçalves, Rosana F.; Figueiredo, José T. O.; De Figueiredo, Alberthmeiry T.; Li, Maximo Siu; Longo, Elson [UNESP]; Godinho, Mario J. (Royal Society of Chemistry (RSC), 2013)
A YSZ@Al2O3 nanocomposite was obtained by Al 2O3 coating on the surface of yttrium stabilized zirconia via a polymeric precursor method. The resulting core-shell structures were characterized by X-ray diffraction, scanning electron microscopy, transmission electronic microscopy and PL spectra. The TEM micrographs clearly show a homogeneous Al2O3 shell around the ZrO2 core. The observed PL is related to surface-interface defects. Such novel technologies can, in principle, explore materials which are not available in the bulk single crystal form but their figure-of-merit is dramatically dependent on the surface-interface defect states. © 2013 This journal isThe Royal Society of Chemistry.